Stalking - Rudrappa, D; Kumar, MP; Chandrashekar, TN (International Journal of Medical Toxicology and Forensic Medicine, 2014)
Stalking is a term commonly used to refer to unwanted or obsessive attention by an individual or group toward another person. Stalking behaviors are related to harassment and intimidation and may include following the victim in person or monitoring them. According to a 2002 report by the National Center for Victims of Crime “Virtually any unwanted contact between two people [that intends] to directly or indirectly communicates a threat or places the victim in fear can be considered stalking" although in practice the legal standard is usually somewhat stricter. The effects of stalkers on their victims are immense and can result in significant psychiatric morbidity. Only recently, however, has the behaviour become the subject of scientific study, and research remains in its infancy.